Limiting Resources : Market-Led Reform and the Transformation of Public Goods - Haglund, LaDawn, 1968- (Book collections on Project MUSE., 2010)
"Using empirical evidence from Costa Rica and El Salvador, outlines alternative principles underlying water and electricity provision, including social rights, accountability, and environmental sustainability. Argues that an excessive market orientation marginalized these principles while weakening state structures and accountability mechanisms and benefiting a small group of elites" --Provided by publisher.